Lymphoid peritoneal fluid as a variant of chylous-like effluent in peritoneal dialysis: proposal for a new diagnostic term (2024)
The cloudy bag in peritoneal dialysis is generally associated with infectious peritonitis and non-infectious etiologies. These cloudy bags may have increased cellularity or low/acellular counts. In the case of low cell count, the concomitant detection of fibrin or fat can provide guidance on its etiology. The cloudy peritoneal bag with a whitish appearance is usually due to its high fat content (chyloperitoneum). The etiologies include pharmacological, traumatic or inflammatory causes. The elevated fatty component in chyloperitoneum may be triglycerides (chylous), cholesterol (pseudochylous) or lymph. We present the case of a patient with stage 5 chronic kidney disease (CKD). He starts continuous ambulatory peritoneal dialysis and presents turbid but acellular peritoneal effluent with chylous appearance, negative cultures, and low levels of triglycerides and cholesterol on physicochemical evaluation. It doesn’t meet the criteria for chylous or pseudochylous fluid, which is why the term lymphoid fluid is here proposed to describe it, because of its resemblance to lymphatic fluid in color. To our knowledge, this is the first case in the literature to report this effluent (milky-looking fluid without high levels of triglycerides or cholesterol) and to propose a specific term to describe it.